Bureaucracy Entrepreneurship Strategy Waste Management In Ciamis, Tasikmalaya, Pangandaran Regency And Tasikmalaya, Banjar City (Journal of Namibian Studies : History Politics Culture, 2023)
The limited quantity of human resources and inadequate service and bureaucracy in waste management services in East Priangan have made waste management in the area very ineffective. The lack of facilities and infrastructure, public awareness, and the absence of rules and strategies in waste management then exacerbate this. This study then aims to see how the entrepreneurial strategy of waste management bureaucracy can be implemented in East Priangan, Indonesia. This research is descriptive qualitative research using SWOT analysis. The data used in this study came from interviews and literature studies regarding studies that still relate to the research discussion. The results of this study then found that waste management in East Priangan uses five strategies, where the Core Strategy and cultural strategy are going well, while the Consequence Strategy, Customer Strategy, and Control Strategy can be said to be not optimal. The strategy for entrepreneurship in the waste management bureaucracy that is effective in East Priangan is an Aggressive Strategy (Growth Oriented Strategy), meaning that the organization is in a steady state by maintaining the previous strategy and seeking necessary improvements to be further optimized through internal strengthening or future innovation.